Adhesion characteristics and spectroscopic analysis of regenerated ultraviolet aged asphalt binder using waste vegetable oil - Bo Li; Jie Han; Xueli Nan; Xiaolan Li; Xiaomin Li; Peng Zhang (Case Studies in Construction Materials, 2023)
The adhesion characteristics between asphalt and aggregate are damaged severely after ultraviolet (UV) aging. Thus, the adhesion characteristics of UV-aged asphalt after regeneration should be investigated. The regenerated UV-aged asphalt was prepared according to different influencing factors (aging asphalt with UV for different amounts of time, different rejuvenator content, and different stirring temperatures and stirring times). Using the surface free energy (SFE) theory, the effects of the four influencing factors above on the adhesion characteristics of regenerated UV-aged asphalt were investigated. Fourier Transform Infrared Spectroscopy (FTIR) was used to analyze the functional group changes of different types of regenerated UV-aged asphalt. The results indicated that the regenerated asphalt under different preparation conditions exhibited different regeneration effects. The SFE showed that the asphalt’s adhesion improved after regeneration and its resistance to water damage increased. Further, an appropriate increase in the stirring temperature and stirring time improved the regenerated asphalt’s adhesion. It was concluded from the FTIR analysis that the homemade rejuvenator diluted the carbonyl and sulfoxide groups in the aged asphalt and restored some of the asphalt’s properties. In addition, the correlation between the SFE index and carbonyl group correction peak area was analyzed. The correlation between the peak area and the peeling work at different stirring temperatures was 0.98. Therefore, regenerated asphalt’s adhesion can be evaluated effectively with SFE and FTIR.